The effect of 6-Methoxy-2-Benzoxazolinone (6-MBOA) on indoleamine regulation and its possible role in depression - Tanda, Sindiswa Eunice (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2000)
Tryptophan is an essential amino acid that is obtained from the diet. Approximately 98 % of ingested tryptophan is metabolized by the enzyme tryptophan 2,3-dioxygenase (TDO). The metabolism of tryptophan by TDO is an important determinant of tryptophan bioavailability to the brain for serotonin (5-HT) biosynthesis, an essential amine in affective disorders such as depression. Studies done on circadian rhythmicity of the enzyme activity have shown that, TDO activity is high during the scoto-phase (dark-phase), which is attributable to the de novo enzyme synthesis that occurs during this phase. 6-Methoxy-2-benzoxazolinontr-(6-MBOA), a structural analogue of melatonin (aMT) was shown to inhibit TDO activity in both the photo-phase (light-phase) and the scoto-phase with greater potency during the light-phase. Further studies were directed at demonstrating the effects of 6-MBOA on the brain tryptophan hydroxylase (TH) activity, which is a rate limiting enzyme in 5-HT biosynthesis and subsequently on 5-HT levels. The findings showed that, 6-MBOA induces TH activity with a concomitant rise in brain 5-HT levels. The blockade of 5-HT re-uptake into the presynaptic neuron leads to an increase in 5-HT available for the stimulatory action of 5-HT receptors. An attempt to establish whether the administration of 6-MBOA would block the binding of 5-HT to receptors on the synaptosomal membrane showed that 6-MBO A only inhibits the binding of 5 -HT at specific concentrations. In view of the positive effects imposed by 6-MBOA on brain 5-HT levels, urinary 5-hydroxyindole acetic acid (5-HIAA) excretion was measured before and after treatment with 6-MBOA. 5-HIAA excretion was found to be significantly increased after 6-MBOA treatment. Extensive research on the biosynthesis of pineal metabolites has been conducted in the past two decades. The pineal metabolites are synthesized from the precursor tryptophan. In order to obtain an overall picture of the effect of6-MBOA on pineal indole metabolism, an organ culture technique was employed. The results obtained showed that although 6-MBOA administration to rats caused a significant increase in aMT production, there was an insignificant increase in NAS production. This is an immediate precursor of aMT. Other pineal indoles were not affected at all by 6-MBOA administration. Furthermore, the production of pineal NAS and aMT showed an inter-individual variation with some animals producing very high, some very low and some produced average levels of these two metabolites in both photo and scoto-phase experiments. A study undertaken to investigate the circadian rhythm in endogenous aMT production using the competitive ELISA technique showed a clear pattern with high levels of aMT produced during the dark-phase and low levels ofaMT produced during the light-phase. Furthermore, the administration of6-MBOA to rats lead to a significant rise in endogenous aMT production.
Keywords: Tryptophan -- Physiological effect; Tryptophan -- Therapeutic use; Antidepressants